Analisis Kesalahan Imla’ Mahasiswa Program Studi Pendidikan Bahasa Arab IAIN Salatiga - Muh. Hafidz; Roviin (Universitas Yudharta Pasuruan, 2020)
Imla’ is one of the elements of Arabic language with a quite complex in writing, this problem is also faced by students of the Arabic Language Study Program at the State Islamic Institute of Salatiga. In this research, Imla's errors were collected through a written test. The analysis steps are carried out in three steps, first; collecting language errors data, second; identifying and classifying language errors, third; explaining language errors and the correct language standards. Based on the analysis, the results are; 1). The error in writing letters that are similar in a word, 2). Lack of writing hamza washal on words that should begin with hamza, 3). The error in writing al syamsiya on words that should not be written with al syamsiya, 4). The error in writing ta' marbutha, 5). The error in writing the mark of hamza in words beginning with the mark of hamza qatha', 6). The error in writing hamza in the middle of a word, 7). The error or lack of alif tafriq, 8). The error in writing alif layyina in the middle of a word, 9). The error in writing ta 'marbutha on certain words that should be written with ta' maftuha.